Development of soft skills and entrepreneurial intention in university students - Aledo Ruiz, María Dolores (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Entrepreneurial education has experienced a significant boom in recent years, and it is essential that universities promote an entrepreneurial culture to optimize the employability of their students. This paper aims to study the impact of entrepreneurial education on soft skills and the entrepreneurial attitude of two groups of students: control group (Social Sciences area) and experimental group (Health Sciences area), developing business plans. The results show that this experience contributes to arouse the entrepreneurial intention of the students and helps them acquire soft skills to improve their talent.